Telomerase activity correlates with tumor aggressiveness and reflects therapy effect in breast cancer - Hoos, Axel; Hepp, Hedwig H.; Kaul, Sepp; Ahlert, Thorsten; Bastert, Gunther; Wallwiener, Diethelm (International journal of cancer, 1998)
Telomerase appears to be an important factor for the control of cellular proliferation capacity and for tumorigenesis. Enzyme activity is highly increased in almost all human tumors and distinguishes them from benign lesions. Besides its diagnostic value, telomerase activity appears to be associated with tumor progression. The purpose of our study was to evaluate the significance of telomerase activity as a clinical marker in breast cancer. Twenty-five tumor samples from breast cancer patients were analyzed retrospectively for telomerase activity in chemotherapy-treated and untreated tumors. For each patient an identical number of cells was measured quantitatively for telomerase activity using the Telomerase-PCR-ELISA based on the TRAP (telomerase repeat amplification protocol) method. The findings were compared to clinical course, therapy and staging parameters. Telomerase activity was detected in all breast cancers. A significant correlation was found between enzyme activity and tumor size, lymph node status and stage: with ongoing tumor progression, telomerase activity appeared to increase in primary carcinomas. No correlation was seen between enzyme activity and the clinical course of patients. Without exception, telomerase activity was strongly decreased in all chemotherapy-treated tumors compared to untreated tumors. Our preliminary data indicate that telomerase activity is associated with aggressiveness of breast tumors and appears to mirror the anti-proliferative effects of chemotherapy. Int. J. Cancer (Pred. Oncol.) 79:8-12, 1998.© 1998 Wiley-Liss, Inc.